Photocatalytic degradation of organic dye using titanium dioxide modified with metal and non-metal deposition. (January 2016) - Anas, Muhammad; Han, Dong Suk; Mahmoud, Khaled; Park, Hyunwoong; Abdel-Wahab, Ahmed
Abstract: In this study, photocatalytic degradation of methyl orange (MO) as an example of organic dye was investigated using different wt% Pd-loaded and N-doped P-25 titanium dioxide (TiO2 ) nanoparticles, as example of metal and nonmetal-doped TiO2, respectively. The Pd-loaded and N-doped TiO2 photocatalysts were prepared by post-incorporation method using K2 PdCl4 and urea, respectively, as precursors. A variety of surface analysis techniques were used for characterization of surface and functional group while using ultraviolet/visible (UV–vis) analysis for monitoring photocatalytic degradation of MO. Kinetic parameters were obtained using Langmuir-Hinshelwood model to determine the degradation rate constants. It was found that the metal-loaded titanium dioxide degraded MO in water at a higher rate than did non-metal-loaded titanium dioxide fabricated by using the post-synthesis method. Also, the pure P25-TiO2 degraded MO more than N-doped TiO2 because of decreased surface area by particle agglomeration after being made by the post-incorporation method.